1997
DOI: 10.1108/02656719710170747
|View full text |Cite
|
Sign up to set email alerts
|

TQM in higher education ‐ a review

Abstract: Posits that the role that quality plays in the higher education sector is becoming more important as the dominance of market‐orientation leaves no alternative for universities and colleges but to improve their quality while increasing efficiency. Philosophies like total quality management (TQM), which have been successfully adopted in commercial organizations, are generally seen as the way forward. Includes a review of the published literature on theories and applications of TQM in higher education. The case s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(124 citation statements)
references
References 27 publications
2
113
0
7
Order By: Relevance
“…Taylor and Hill (see Owlia and Aspinwall, 1997, p. 530) state that team working is not common in higher education, although Owlia and Aspinwall (1997) found, when investigating TQM implementation in US universities, that employee involvement and team working were adopted in 86 per cent of cases. Moeller and Sonntag (2001) identified that dysfunctional group membership or ineffective group dynamics impeded the success of self-assessments.…”
Section: Staff Involvement and Teamworkmentioning
confidence: 99%
“…Taylor and Hill (see Owlia and Aspinwall, 1997, p. 530) state that team working is not common in higher education, although Owlia and Aspinwall (1997) found, when investigating TQM implementation in US universities, that employee involvement and team working were adopted in 86 per cent of cases. Moeller and Sonntag (2001) identified that dysfunctional group membership or ineffective group dynamics impeded the success of self-assessments.…”
Section: Staff Involvement and Teamworkmentioning
confidence: 99%
“…According to Fryer, Antony and Douglas (2007), Youssef and Zairi (1995) used 22 generic critical factors in a survey conducted in different parts of the world, Khoo and Tan (2002) found 34 critical success factors for the implementation of quality in the Russian manufacturing industry, Owlia and Aspinwall (1997) produced a "shorter" list of 10 critical factors in a study in the higher education field, and the final example is Karuppusami and Gandhinathan (2006) who extracted 42 critical success factors from 37 previous studies.…”
Section: The Number Of Factors That Were Considered Criticalmentioning
confidence: 99%
“…When focusing on teaching, the voice of customer (VOC) can be utilized to find the right measures for quality (Hwarng and Teo, 2001). One of the main obstacles for this tool's application are the identification of the process "customers" and their concrete requirements (Andreassen, 1994;Owlia and Aspinwall, 1997). For the analysis of the customer's voice, internal and external process stakeholders have to be considered (Elias, 2016).…”
Section: Research Backgroundmentioning
confidence: 99%